2015
DOI: 10.1186/s40814-015-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating return to work through early specialist health-based interventions (FRESH): protocol for a feasibility randomised controlled trial

Abstract: BackgroundOver one million people sustain traumatic brain injury each year in the UK and more than 10 % of these are moderate or severe injuries, resulting in cognitive and psychological problems that affect the ability to work. Returning to work is a primary rehabilitation goal but fewer than half of traumatic brain injury survivors achieve this. Work is a recognised health service outcome, yet UK service provision varies widely and there is little robust evidence to inform rehabilitation practice. A single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Even though returning to work has proven important for long-term ABI survival and increased levels of quality of life [ 10 ], standardized evidence-based VR programs targeting patents with ABI have been lacking [ 11 13 ]. One very interesting feasibility randomized controlled trial (RCT) protocol has been published regarding brain injury and return to work; however, this protocol involved patients with a traumatic brain injury exclusively [ 14 ]. It has previously been shown that support from specialized VR teams help patients with ABI returning to work post injury [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though returning to work has proven important for long-term ABI survival and increased levels of quality of life [ 10 ], standardized evidence-based VR programs targeting patents with ABI have been lacking [ 11 13 ]. One very interesting feasibility randomized controlled trial (RCT) protocol has been published regarding brain injury and return to work; however, this protocol involved patients with a traumatic brain injury exclusively [ 14 ]. It has previously been shown that support from specialized VR teams help patients with ABI returning to work post injury [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were people aged 16 years or above, admitted to one of three major trauma centres for 48 hours or more, with a new TBI (within 8 weeks) and who were in paid or unpaid work or full-time education prior to injury. Full eligibility criteria in the FRESH RCT are explained elsewhere (46). Clinical records and intervention session case report forms (CRFs) were collected for every intervention participant (n = 38).…”
Section: Methodsmentioning
confidence: 99%
“…The intervention has been informed by similar interventions previously developed by our team for patients with traumatic brain injury and stroke [60,61]. It has been developed by a multi-disciplinary team comprising OTs, clinical and neuropsychologists, a psychiatrist, vocational rehabilitation experts, a general practitioner, specialists in rehabilitation and trauma medicine, social scientists and patient representatives.…”
Section: Data To Address Objectivementioning
confidence: 99%